2011
DOI: 10.1111/j.1462-2920.2011.02646.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of key genes for type II secretion in Legionella pneumophila

Abstract: Given the role of type II protein secretion system (T2S) in the ecology and pathogenesis of Legionella pneumophila, it is possible that this system is a target for adaptive evolution. The population genetic structure of L.pneumophila was inferred from the partial sequences of rpoB and from the complete sequence of three T2S structural components (lspD, lspE and pilD) and from two T2S effectors critical for intracellular infection of protozoa (proA and srnA) of 37 strains isolated from natural and man-made envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 98 publications
2
19
0
Order By: Relevance
“…pneumophila had been reported to be clonal and lack of recombinations based on MLEE and SBT data in some studies (Coscolla et al, 2006;Edwards et al, 2008;Gomez-Valero et al, 2009;Smith et al, 1993). However, frequent recombination events were reported in dotA gene (Costa et al, 2010), Type II secretion system genes (Costa et al, 2012), certain intergenic fragments (Coscolla and Gonzalez-Candelas, 2007) and genomic levels as well (Gomez-Valero et al, 2011). A recent study involving 838 STs of L. pneumophila also identified reliable combination events in the SBT loci, and the r/m ratio in this dataset was 16.3, much higher than our study (Underwood et al, 2013).…”
Section: Recombinations In L Pneumophila Isolatesmentioning
confidence: 89%
“…pneumophila had been reported to be clonal and lack of recombinations based on MLEE and SBT data in some studies (Coscolla et al, 2006;Edwards et al, 2008;Gomez-Valero et al, 2009;Smith et al, 1993). However, frequent recombination events were reported in dotA gene (Costa et al, 2010), Type II secretion system genes (Costa et al, 2012), certain intergenic fragments (Coscolla and Gonzalez-Candelas, 2007) and genomic levels as well (Gomez-Valero et al, 2011). A recent study involving 838 STs of L. pneumophila also identified reliable combination events in the SBT loci, and the r/m ratio in this dataset was 16.3, much higher than our study (Underwood et al, 2013).…”
Section: Recombinations In L Pneumophila Isolatesmentioning
confidence: 89%
“…It will be interesting to more systematically assess substrate genotypes among different species as this may give clues to evolutionary relationships. A molecular evolution analysis of (just) L. pneumophila strains has already concluded that ProA and SrnA have been selected due to their role in virulence mechanisms (83). …”
Section: Discussionmentioning
confidence: 99%
“…This lifestyle, namely the interaction with different protozoan in different environments, may have prevented host-specialization and be responsible for the evolutionary story of L. pneumophila [13] . Several studies showed that L. pneumophila clinical isolates showed less genetic diversity than man-made and natural environmental isolates [14] [19] . This evidence supports the hypothesis proposed by Coscollá and González-Candelas [16] that isolates of L. pneumophila recovered from clinical cases are a limited, non-random subset of all genotypes existing in nature, perhaps representing an especially adapted group of clones.…”
Section: Introductionmentioning
confidence: 99%